Ответы и объяснения

Лучший Ответ!
2013-04-13T11:06:06+04:00

sin^2 3x+3 cos^2 3x-4 sin (П/2+3х) cos(П/2+3х)=0

sin^2 3x+3(1- sin^2 3x) -2 *2sin2(П/2+3х)=0

sin^2 3x+3-3sin^2 3x - 4cos2x = 0

-2sin^2 3x - 4( cos^2 x-sin^2 x)= 0

-2sin^2 3x -4cos^2 x + 4sin^2x=0

2sin^2 x -4(1-sin^2x)=0

2sin^2 x - 4 +4sin^2 x=0

6 sin^2 x=4

sin^2x=4/6

sin^2 x=2/3 

sinx=2/3                                 sinx=-2/3

x=(-1)^n arcsin(2/3)+Пn      x=(-1)^n arcsin(-2/3)+Пn

                                                 x=(-1)^n -arcsin(2/3)+Пn

                                                 x=(-1)^n+1 arcsin(2/3)+Пn